Partial Purification and Characterization of Bacillus pumilus Xylanase from Soil Source - Monisha, R.; Uma, M.V.; Krishna Murthy, V. (Kathmandu University Journal of Science, Engineering and Technology, 2009)
Hydrolysis of xylan, the chief type of hemicellulose, is achieved by endo-1,4-β-xylanase and β-xylosidase among other such enzyme complexes. These enzymes are mainly produced by fungi, bacteria, etc. Xylanase finds applications in animal feed, manufacture of bread, beverages, textiles, bleaching cellulose pulp, ethanol, and xylitol production. Xylanase depolymerizes xylan molecules into xylose units, a primary carbon source for bacteria and fungi. In this study, we obtained a bacterial isolate exhibiting good extracellular xylanase activity by screening several soil samples. The bacterium identified was Bacillus pumilus. The isolate produced xylanase demonstrating maximal activity at 35°C and at pH 7.0. Crude extract fractionated by ammonium sulfate precipitation had a specific activity of 0.69 µM min-1 mg-1. Enzyme kinetics and properties were studied by DNS assay method. Xylanase had Km of 4.0 mg ml-1 and Vmax of 0.068 × 10-4 mM min-1 mg-1. Molecular weight of xylanase was 19 kDa as determined on SDS PAGE. The enzyme was partially purified to a fold of 3.79 and a yield of 66%, suggesting the method with fine-tuning could be suitable for scale-up process.